Primary Pre-Extensively Drug-Resistant (Pre-XDR) Tuberculosis with Meningoencephalitis in Nineteen Years Old Young Woman : A Case Report - Sugiri, Yani Jane Rosihaningsih; Tantular, Rezki; Falyani, Silvy Amalia; Maulana, Uray Riki Arif (Malang Respiratory Journal, 2024)
Introduction. Mycobacterium tuberculosis (MTB) is continually evolving in order to resist treatment. This has resulted in drug-resistant tuberculosis, which has a greater rate of therapy failure and mortality, as well as the necessity for other ways of disease transmission prevention. Pre-extensively drug-resistant tuberculosis (Pre-XDR TB) is caused by MTB strains that are resistant to isoniazid, rifampicin, and any fluoroquinolone medicines. Case Report. A 19-year-old HIV-negative immunocompetent female presented to our emergency department with dyspnea and severe headache. She also complained of a cough, a low-grade temperature, and weight loss. She has no relevant medical history and has never been exposed to tuberculosis. A chest X-ray revealed infiltrates with cavities and fibrosis in both lungs, while a brain CT suggested meningoencephalitis. We performed a sputum drug sensitivity test and discovered that this patient was resistant to rifampin, isoniazid, levofloxacin, and moxifloxacin. She was later diagnosed with Pre-XDR TB and was given a tailored lengthier regimen that included Bedaquiline, Cycloserin, Linezolide, Clofazimine, and Etambutol. Her symptoms improved significantly as a result of this program. Discussion. Primary pre-XDR TB in an immunocompetent patient is uncommon, and our case is even more unusual due to meningoencephalitis involvement. The treatment of pre-XDR TB requires a personalized regimen that is tailored to the patient's clinical status and comorbidities. The possibility of transmission via a positive contact was raised in this patient, prompting us to conduct a more thorough contact inquiry to prevent future spread. Conclusion. In our region, there is a risk of'silent' drug resistant tuberculosis. Early detection and treatment of such patients are critical to preventing uncontrollable pan-resistant TB. Successful management with cautious contact investigation will minimize the mortality rate and spread rate of drug-resistant TB. Keywords. Drug-Resistant Lung Tuberculosis, Drug-Resistant Meningoencephalitis Tuberculosis